(untitled) (Environment & Health, 2022)
Objective: We established and scientifically substantiated the psychohygienic principles of using health-preserving technologies in modern institutions of higher education. Materials and methods. The research was conducted on the basis of National Pyrohov Memorial Medical University. A well-structured set of highly informative modern hygienic, medical-sociological, psychophysiological and psychodiagnostic methods and methods of statistical analysis were used to adequately achieve this goal. Results. The data obtained in the course of research indicate that as conceptual psychohygienic principles of effective use of health-preserving technologies in modern institutions of higher education should be noted: (1) regime-adaptive principle of application of psychohygienic components in the structure of modern health-preserving technologies, which determines the need to take into account the main regime elements of educational and extracurricular activities of students in specific conditions of the educational process, determining and constantly monitoring the level of educational adaptation and academic performance of students, especially in professionally oriented disciplines; (2) psychophysiological principle of application of psychohygienic components in the structure of modern health technologies, which is determined by the level of development of leading socially and professionally significant psychophysiological functions of the body of girls and boys; (3) personal principle of application of psychohygienic components in the structure of modern health technologies, which is related to the peculiarities of assessing the processes of formation of leading personality traits of student youth, which play an important role under the influence of both favorable and, above all, unfavorable educational factors. extracurricular activities; (4) integrative-functional principle of application of psychohygienic components in the structure of modern health technologies, which is determined by the presence of deep relationships between individual components of the functional state and adaptive capacity of young girls and young boys, which have a complex impact on health and theoreticalу- and, mainly, practically-significant components of students’ training. Conclusions. In the course of the research the leading psychohygienic principles of using health-preserving technologies in modern modern institutions of higher education have been identified and scientifically substantiated.